Nickel oxide nanopetal-decorated 3D nickel network with enhanced pseudocapacitive properties1. Issue 20 (6th March 2015) - Cheng, Guanhua; Bai, Qingguo; Si, Conghui; Yang, Wanfeng; Dong, Chaoqun; Wang, Hao; Gao, Yulai; Zhang, Zhonghua
<x xml:space="preserve">Abstract</x> Calcination of anodized nickel foam has been used to synthesize NiO nanopetals electrodes with enhanced electrochemical performance.